PENERAPAN MODEL PROBLEM BASED INTSTRUCTION (PBI) DALAM MENINGKATKAN KEMAMPUAN MENULIS ARTIKEL PADA MAHASISWA PRODI D4 K3 STIKES BHAMADA SLAWI - Dwi Armoko (Universitas Pancasakti Tegal, 2018)
This study aims to determine the differences in learning outcomes act of writing articles before and after using the model Problem Based intstruction (PBI) in the 1st semester students Occupational Safety and Health Study Program. This research is a research of sex experiment with single pretest and posttest group design (One Group Pretest Posttest Design). The design only looks at student learning outcomes before and after treatment with Problem Based Intstruction (PBI) modeling in single group. Population and sample of this research are students of 1st semester Occupational Safety and Health Study Program STIKes Bhamada Slawi. While the test that will be used to measure the ability of students is the ability to write an article. The test is made in the form of a description. Learning outcomes were tested using the Liliefors normality test, and tested the hypothesis with the -t test. Based on the calculation of normality data is done, then obtained t count (th) of 36.047 dengandf 20 and p value of 0.000. The p value is smaller than the 5% significance level (p = 0,000 <0.05). Thus, the t-test results show that there is a difference in the ability to write articles between before and after applying the Problem Based Instruction (PBI) learning model.